Addition of a silyl ketene acetal to alpha,beta-unsaturated cyclic anhydrides - Gnaneshwar, Rudhramyna; Sivaram, Swaminathan (Synthetic Communications, 2010)
Addition of [1-methoxy-2 methyl-1-propenyl)-oxy] trimethylsilane (MTS) to unsymmetrical ,-unsaturated cyclic anhydrides (namely, itaconic anhydride and citraconic anhydride) as well as symmetrical anhydrides (namely, maleic anhydride and 2,3-dimethylmaleic anhydride) was investigated. Itaconic anhydride isomerizes to citraconic anhydride in the presence of MTS. In the presence of Lewis acid catalysts (Yb(OTf)3/CH2Cl2), MTS adds to itaconic anhydride at room temperature in a 1,4-fashion. 1,2-Addition is the preferred pathway with both 2,3-dimethyl maleic anhydride and citraconic anhydride.
Keywords: 1; 2-Addition; 4-addition; cyclic anhydrides; Lewis acid; Silyl ketene acetal

Bidentate ligand-catalyzed enantioselective addition of RZnX to benzaldehyde - Jagtap, Ravindra S.; Joshi, Navalkishore N. (Tetrahedron Letters, 2011)
{Enantioselective addition of RZnX (R = alkyl
Keywords: 1; 2-Addition; Asymmetric synthesis; Chelating ligands; Organozinc